Emotions in Advertising and Their Connection to Consumers - Rocha-Vilca, Liliana (2024)
This study aimed to analyze the reception of the transmission of the “virtual mass” among the Catholic faithful in Lima. It was positioned in the qualitative phenomenological paradigm. An online questionnaire was conducted with 1,235 Catholic faithful from the city of Lima (Peru). Some faithful considered the advantages of the “virtual mass” to be its greater reach, saving time and money, and the possibility of seeing the celebration repeatedly, among others. The disadvantages indicated were idleness, laziness, lack of commitment, the possibility of distraction, and the absence of community. The majority of participants considered that the “virtual mass” is not equivalent to the in-person celebration.